The Impact of Frictions in Routine Execution on Economies of Scope - Brahm, Francisco; Tarzijan, Jorge; Singer, Marcos (Strategic Management Journal, 2017)
[Research summary: Based on a detailed database of a beverages producer-distributor that expanded its product variety by leveraging its logistic network, we show that product diversification generates economies of scope and also higher operational costs. The result is an inverted-U relationship between variety and productivity: When the firm offers few additional categories, productivity grows, but as the number of categories rises, the costs of executing the operational routines increase rapidly and productivity falls. The negative effect on productivity increases if the added product category is more dissimilar to previous ones, and decreases with learning from operational experience. Our results highlight how frictions at the operational level can limit the benefits of diversification, even in the absence of other sources of diseconomies, such as increased coordination needs. Managerial summary:One of the prevalent reasons for companies to expand to adjacent product lines is attaining economies of scope. However, such growth strategy also generates operational frictions, even if the day-to-day routines do not appear to change at all. Product diversity is disruptive for routine execution, as it requires coordination and exception handling, and may ultimately overcome any efficiency obtained from growth. We estimate the relevance of such operational friction using data from a beverages distribution network. When product variety is low, additional categories do generate efficiency, but after reaching a given threshold, friction prevails. We find that operational friction increases when products aremore dissimilar, but is attenuated when workers learn from their own and other’s experience.]